Dynamics and distribution of weed species in weed associations - MARINOV-SERAFIMOV, PLAMEN; GOLUBINOVA, IRENA; VASILEVA, VILINANA (The Indian Journal of Agricultural Sciences, 2019)
Dynamics of weed density with a natural background of weeds in agrophytocenoses of sainfoin (Onobrychis sativa L.), birdsfoot trefoil (Lotus corniculatus L.) and alfalfa (Medicago sativa L.), pure grown (100%) and in mixtures with cocksfoot (Dactylis glomerata L.) (50:50%) and sown under a cover of pea (Pisum sativum L.) were tested in field trial in the Institute of Forage Crops, Pleven, Bulgaria. It was found that the weed infestance and species composition changed depending on the type of Ðµdificator. The species composition in weed associations was the highest in pure grown Lotus corniculatus L. In mixtures of Onobrychis sativa L. + Dactylis glomerata L. the highest weed infestance was recorded, and the lowest in Onobrychis sativa L. under cover of Pisum sativum L. Weed infestance in mixtures was lower as compared to pure grown swards, except Medicago sativa L. + Dactylis glomerata L. For the specific environment of study the highest part for annual dicotyledonous weed species (from 0.0 to 49.5%), followed by perennial dicotyledonous (from 3.7 to 58.2%) was obsereved. There was a strong variation in the percentage in agrophytocenoses of Convolvulus arvensis L. (from 0.0 to 11.4%), Sonchus arvensis L. (from 0.0 to 19.0%) and Erigeron canadensis L. (from 0.0 to 47.8%), whereas Matricaria recutita L. varied within narrow range (0.0 to 3.7%). The dependance allows to be used for developing more effective weed control systems in the studied forage crops and mixtures.